Analisis Kausalitas Belanja Modal, Bantuan Sosial dan Indeks Pembangunan Manusia - Rahmi Handayani; Ahmad Soleh; Agus Santoso; Yunie Rahayu (Universitas Batanghari, 2022)
Human development is the spearhead in development planning. To measure how much human development achievements are used, the Human Development Index (HDI) indicator is used. The higher the HDI value in one region, the better the level of welfare in the region. So often HDI is considered to have been able to represent the level of welfare of the population, because in HDI includes elements that include economic and non-economic variables. To sustain the human development process, there needs to be an allocation in financing. The amount of capital expenditure and social assistance spending certainly has a close relationship with human development indexes. Based on data from BPS Jambi Province shows an interesting phenomenon where Capital Expenditure and Social Assistance Spending fluctuate every year but HDI always increases. On the basis of these problems, this research is very important and interesting to do. The purpose of this study is to analyze conditions, Causality Relations (reciprocity), Capital Expenditure, Social Assistance Spending and Human Development Index (HDI), as well as hdi response due to shocks from capital expenditure and social assistance spending. This research uses qualitative and quantitative descriptive analysis with a library reseach approach, using secondary data in the form of panel data sourced from the financial statistics reports of local governments and the Central Statistics Agency (BPS) as well as other relevant agencies and literature during the period 2010-2019 in 11 districts / cities in Jambi Province. Analytical tools used to describe the condition of capital gains, social assistance and HDI are used growth models, and analytical tools to analyze causality relationships and HDI responses due to Capital Expenditure and Social Assistance Spending are used VAR (Vector Autoregression) models. The results showed that the condition of capital expenditure, social assistance and HDI in regencies / cities in Jambi Province experienced a positive trend. There is a one-way causality relationship between dependent variables and independent variables and in the research period if there is a shock or shock in Capital Expenditure and Social Assistance Spending it will affect the Kab / Kota Human Development Index in Jambi Province.